Petrochemistry of Phyllites from Patharkhola, Lesser Kumaun Himalaya with Reference to Tectonic Implications - Rana, Haritabh; Thomas, Harel; Soni, Aman; Shukla, Satyam (Earth and Planetary Science, 2023)
Phyllites from Patharkhola, Lesser Kumaun Himalaya have been studied to investigate the geochemical characteristics of these rocks and their formation processes and mechanism of emplacement. Petrographically, phyllites have been showing the mineral assemblages as Biotite (25% approx.)-chlorite (25% approx.)-muscovite (20% approx.)-quartz (10% approx.)-feldspar (10% approx.)-sericite (5% approx.). Geochemically, the analysed four samples of phyllites have high SiO2 and Al2O3 values. Phyllites with higher alumina have more enrichment of trace elements. The enrichment of Zr and depletion of Y and Nb indicate preferential survival of zircon in extreme weathering conditions. The HFSE has shown variation in the ratios due to decoupling with the major oxides. The enrichment of LREE and depletion of HREE suggest mixing of the terrigenous sediments with the concominant magma. Discrimination plots to classify the tectonic settings suggested that the phyllites of Patharkhola have formed in active continental margins. ER